Analisis Rasio Profitabilitas dalam Menilai Kinerja Keuangan pada PT. XL Axiata Tbk yang Go Public di Bursa Efek Indonesia Periode 2021-2023 - Astri Wahyuni; Mariam Makmur; Ari Ayu (Journal Economic Excellence Ibnu Sina, 2025)
A company's financial performance is one of the main indicators in assessing the health and sustainability of a business entity's operations. Evaluation of financial performance is crucial, especially for large companies operating in strategic sectors such as telecommunications. PT. XL, as a telecommunications company listed on the Indonesia Stock Exchange, requires regular performance assessments to provide a clear picture of the effectiveness of its business strategy and its ability to generate profits. This study aims to analyze PT. XL's financial performance using a profitability ratio approach. The research method used is descriptive quantitative, utilizing secondary data sourced from the company's financial statements, including the balance sheet, income statement, and other financial statements for the 2021–2023 period. The profitability ratios analyzed include Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), and Earnings Per Share (EPS). These five ratios were chosen because they are able to describe the company's ability to generate profits, both in terms of sales, total assets, and shareholder equity. The analysis results indicate that PT. XL's financial performance during the study period is still less than optimal. This is reflected in the profitability ratio, which is below the average standard for the Indonesian telecommunications industry. This condition indicates that the company has not been able to optimally manage its resources to generate competitive profits. This finding has important implications, namely the need to evaluate financial management strategies, operational cost efficiency, and improve service quality to increase company profitability in the future. Therefore, this study confirms that profitability ratio analysis is a crucial instrument for assessing a company's financial condition and serves as a basis for formulating performance improvement strategies.